INNOVATIVE CONTENT OF STUDENT PREPARATION IN HIGHER PEDAGOGICAL EDUCATION (JournalNX - A Multidisciplinary Peer Reviewed Journal, 2021)
The article describes the pedagogical and psychological problems of training future teachers for work in secondary schools. Manifestations of innovative activity of the future teacher are divided into groups (types) and their tasks and areas of knowledge are analyzed.